Bees algorithm for interference suppression of linear antenna arrays by controlling the phase-only and both the amplitude and phase - Guney, K.; Onay, M. (Expert systems with applications, 2010)
In this paper, bees algorithm (BA) has been used for null steering in the antenna radiation pattern by controlling the phase-only and the complex weights (both the amplitude and phase) of the array elements. The BA is an optimization algorithm inspired by the behavior of the honey bees to find the optimal way of harvesting food resources around the hive. Simulation results for Chebyshev patterns with the imposed single, multiple and broad nulls are given to show the effectiveness of the proposed method. The sensitivity of the nulling patterns due to small variations of the element phases is also investigated.